Strategie zachowań politycznych młodzieży w dobie kryzysu (polskiej demokracji) = Strategies of political behaviours of the youth in times of crisis (of Polish democracy) - Szaban, Dorota; Lisowski, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main reason of the authors` interest in political behaviours of the youth was the fact that this category remains politically most passive. For many years the level of interest in politics among young people has been remaining at a stable, low level. The age is also an important dimension of differentiating the opportunities of applying the Internet to political activity.
Keywords: youth; political activity; democracy; internet; information society; młodzież; aktywność polityczna; demokracja; społeczeństwo informacyjne